Development of internet applications for SCADA systems - Ong, Yew Soon. (2008)
The World Wide Web (WWW) has become the most convenient way to access information on the Internet because the WWW browser integrates different network services into a common easily accessible user interface. Internet protocol and its technology are gradually becoming the common standard of many Enterprise's networks, which lead to Intranets and Extranets. These networks are especially suited for accessing information of the Supervisory Control and Data Acquisition (SCADA) system.